Implementasi Pendidikan Rabbani dalam Membentuk Karakter dan Kecerdasan Spiritual - Nasrulloh (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
This paper aims to analyze the implementation of Robbani Education carried out at SDIT SUIS Bogor in shaping the character and spiritual intelligence of students. This type of research is descriptive qualitative with a field study approach. Primary and secondary data sources were collected using in-depth interviews, FGD, observation, and documentation studies. The data analysis technique uses the theory of Miles and Huberman with the stages of data reduction, data presentation, and drawing conclusions or verification. The validity of the data was tested by using the data triangulation method to get the quality of meaning in the interview results. The research findings include that the method of educating by example and habituation alone is not enough to maximize the level of success in character education and spiritual intelligence. The author views that the formation of character and spiritual intelligence will be maximized if using Nashil Ulwan's theory as a whole, namely educating by example, educating by habituation, educating with advice, educating with attention, and educating with punishment.